Late recurrence of cutaneous melanoma: case report - Almeida, Diogo Barata de (2016)
Introduction: Ten-year survival for patients with cutaneous malignant melanoma (CMM) is considered to be synonymous with cure. However, there are reports of late recurrence after this period. This report stresses the importance of awareness of late recurrences and reflects on the role of the family physician (FP) in timely diagnosis. Case description: A 50-year-old man, who was a smoker with history of arterial hypertension and the excision of a CMM at 28 years of age, came to see his FP complaining of a dry cough for two days. An upper respiratory tract infection was diagnosed and treated symptomatically. One month later he returned due to the persistence of the cough. There were no other abnormal signs or symptoms. The cough was presumed to be a side effect of Zofenopril prescribed for control of arterial hypertension. This was stopped and replaced with Irbesartan. He returned two months later with the same complaint. There were no complaints of fever, sweating, chest pain, haemoptysis, or weight loss. Physical examination was normal. The erythrocyte sedimentation rate, ordered by his occupational health doctor, was 87mm/h. The diagnoses of pulmonary tuberculosis or lung cancer were considered. He was referred to the local emergency room, where a thoracic computerized tomography scan was performed. It revealed a proliferative nodular lesion on the left lung apex, compatible with lung cancer. The patient was referred for a pulmonary consultation, and was then admitted to hospital for partial resection of the mass. The histological results showed a metastasis of CMM, 22 years after the initial diagnosis. Comment: There are a growing number of reports of late recurrences of CMM. Early detection should be a concern for physicians. The FP can play an important role on monitoring these cases given the longitudinal continuity of care they provide.